IMPACT OF PHYSICAL AND SPORTS REHABILITATION MEASURES ON QUALITY OF LIFE INDICATORS IN COMBATANTS - Nataliia M. Krushynska; Iryna O. Kohut; Svitlana V. Fedorchuk; Oleksandr I. Korbush; Klavdiia H. Kozakova; Viktoriia B. Zamkevych (Клінічна та профілактична медицина)
Introduction. As the war continues, the number of defenders suffering from physical and/or mental health impairments is steadily increasing. After victory, this number will rise even further, as approximately one million individuals will return home in need of professional support. Studying the quality of life is a pressing and integral issue in the socialization of combatants.